Visitors development from a sociomuseological perspective (Cadernos de Sociomuseologia, 2025)
This work presents a reflection about the relationship between museums and the public as a management aspect of these institutions that became increasingly prominent over time. Several transformations have occurred since museums open to the public has been widely diffused, in the 19th century. Those transformations have resulted in a more visitor-centred approach, in which the concept of Audience Development has become widespread, both in cultural policy and in museum practices. Nonetheless, the concept of Audience Development has quite a broad and ambivalent meaning and is often used in a noncritical way. The duality and the dilemmas surrounding the concept will be addressed from a sociomuseological perspective in a case study analysis of three Brazilian museums: Museu da República, Museu da Língua Portuguesa and Muquifu — Museu dos Quilombos e Favelas Urbanos.Keywords: Sociomuseology; Audience Development; Muquifu — Museu dos Quilombos e Favelas Urbanos; Museu da Língua Portuguesa; Museu da República